Marketing research : text and cases - Boyd, Harper W.; Westfall, Ralph L. ;Stasch, Stanley F. (Homewood, Illinois : R.D. Irwin, Inc., 1981)
In the 25 years since the first edition of this book was published, marketing research has grown tremendously. There has been a continued growth in the sophistication of the statistical methods used, focus group interviews and other relatively unstructured techniques have had a resurgence, psychographic methods in market segmentation studies have grown more popular, and simulated sales models are now being used in new product development work. On the other hand, personal interviews in the home, long the backbone of marketing research, have declined in importance to be replaced by shopping center interviews and telephone surveys.
Part I. Introduction to marketing research -- Part II. Basic concepts -- Part III. The Marketing research process -- Part IV. Selected application of marketing research.
Includes bibliographical references and index.
Keywords: MARKETING RESEARCH